Negative impact of Interleukin-9 on synovial regulatory T cells in rheumatoid arthritis - Chakraborty, Sushmita; Gupta, Ranjan; Hieke-Kubatzky, Katharina; Kar, Santanu; Kraus, Franziska V.; Souto-Carneiro, Maria Margarida; Lorenz, Hanns-Martin; Kumar, Pankaj; Kumar, Vijay; Mitra, Dipendra Kumar (Clinical immunology, 2023)
In Rheumatoid Arthritis (RA), regulatory T cells (Tregs) have been found to be enriched in the synovial fluid. Despite their accumulation, they are unable to suppress synovial inflammation. Recently, we showed the synovial enrichment of interleukin-9 (IL-9) producing helper T cells and its positive correlation with disease activity. Therefore, we investigated the impact of IL-9 on synovial Tregs in RA. Here, we confirmed high synovial Tregs in RA patients, however these cells were functionally impaired in terms of suppressive cytokine production (IL-10 and TGF-β). Abrogating IL-9/ IL-9 receptor interaction could restore the suppressive cytokine production of synovial Tregs and reduce the synovial inflammatory T cells producing IFN-γ, TNF-α, IL-17. However, blocking these inflammatory cytokines failed to show any effect on IL-9 producing T cells, highlighting IL-9's hierarchy in the inflammatory network. Thus, we propose that blocking IL-9 might dampen synovial inflammation by restoring Tregs function and inhibiting inflammatory T cells.
Online verfügbar 23 October 2023, Version des Artikels 29 October 2023
Gesehen am 15.01.2024